MINAT MAHASISWA MENJADI AKUNTAN PUBLIK: MOTIVASI, PERTIMBANGAN PASAR KERJA DAN PENGETAHUAN: Beberapa Perguruan Tinggi Swasta di Palembang - Damayanti, Rika; Mulatsih, Endang Sri; Pratiwi, Nurul Mardiyyah; Aktarina, Destia; Fikriyansyah, Ahmad (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
IAPI indicates that Indonesia faces a deficiency of public accountants. The deficiency of specialists is essential to forecast expansion in the business sector. One of IAPI's objectives for the "CPA Days 2023" program in West Jakarta is to enhance student interest in undertaking the Certified Public Accountant (CPA) examination. This study seeks to elucidate the factors of motivation, labour market considerations, knowledge of public accounting, and student interest in pursuing a career as public accountants, and to determine the effects of these factors on student interest in this professional field. The research employed a quantitative methodology and utilised descriptive and verification analysis techniques Utilizing IBM SPSS Statistics 22.0. The sample of this study were students enrolled in accounting programs at various private institutions in Palembang city, including STIE Mulia Darma Pratama, Muhammadiyah University of Palembang, PGRI University of Palembang, Bina Darma University, Multi Data University, and IBA University. The Slovin formula was employed to ascertain the sample size. The chosen sample consisted of 85 respondents, determined by certain criteria and computed a sample of 85 students was determined using Slovin's formula. This study's findings indicate that the motivation variable (X1) and the job market consideration variable (X2) do not influence student interest in pursuing careers as public accountants, however knowledge of public accountants (X3) positively affects student interest in this profession. The coefficient of determination of 51.7% indicates that motivation variables (X1), labour market considerations (X2), and knowledge of public accountants (X3) account for 51.7% in the variation of student interest in becoming public accountants, while the remaining 48.3% is attributable to extraneous factors not examined in the study.